The influence of different sources of anticipated instrumental support on depressive symptoms in older adults - Fu, Duanduan; Wang, Fang; Gao, Baizhi; Bai, Qin; Liu, Guilin; Zhu, Jinghui (Frontiers in Public Health, 2024)
Objective: This study investigated how anticipated instrumental support sources and intergenerational support influence depressive symptoms in older Chinese adults.We employed binary logistic regression on data from 7,117 adults aged ≥60 in the 2018 China Health and Retirement Longitudinal Study, controlling for gender, marital status, and self-rated health. Results: 38.89% of respondents exhibited depressive symptoms. Anticipated support from spouse and children, spouse only, children only, or other sources showed 52%, 25%, 46%, and 40% lower odds of depression, respectively, compared with no anticipated support. Those providing financial support had 36% higher odds of depression than those without exchanges.However, those receiving financial support, receiving instrumental support, and receiving and providing financial and emotional support had 19%, 14%, 23%, and 24% lower odds of depression. Conclusions: Different anticipated instrumental support sources and intergenerational support influenced depression odds in older adults, suggesting potential benefits in promoting such support systems.